Optical Study on Poly(methyl methacrylate)/Poly(vinyl acetate) Blends - R. M. Ahmed (International Journal of Photoenergy)
Transparent films of poly(methyl methacrylate)/poly(vinyl acetate) blend with different concentrations were prepared by using solution-cast technique. FT-IR transmission spectra were carried for the samples to detect the influence of UV radiation. In addition, optical absorption measurements were carried out for the samples at room temperature across the 190–900 nm wavelength regions before and after exposure to UV and filtered radiation using xenon arc lamp. The study has been also extended to include the changes in the optical parameters including the band tail width and band gap energies for the samples. Moreover, the refractive index was calculated for the samples from specular reflection and absorption spectrum before and after exposure to UV and filtered radiation.